Al-Maḥajja al-bayḍāʾ fī uṣūl al-dīn - al-ʿAnsī, Ḥusām al-Dīn (Miras Maktoob, ISBN: 9789004365452., 2019)
From the time of its foundation in 284/897, the Zaydī Imamate of Yemen was home to Muʿtazilī ideas. During the first centuries and starting with Imam al-Hādī ila ʼl-Ḥaqq (d. 298/911), Zaydī ideology included elements akin to the opinions of the Baghdad School of the Muʿtazila as founded by Bishr b. al-Muʿtamir (d. 210/825). However, in the 5-6th/11-12th centuries, we see a rise in popularity of Bahshamiyya ideas, a sub-group of the Basran School of the Muʿtazila around Abū Hāshim al-Jubbāʾī (d. 321/933). These ideas were systematized and elaborated upon by the Zaydī theologian al-Raṣṣāṣ (d. 584/1188). Among those who resisted Bahshamī ideas to defend the teachings of the earlier imams was the jurist, theologian and author of more than 100 works, Ḥusām al-Dīn al-ʿAnsī (d. 667/1268). This volume contains a facsimile of the largest copy of al-Maḥajja al-bayḍāʾ fī uṣūl al-dīn , al-ʿAnsī's major theological handbook, covering the first four parts out of eight.